Capsule robot for gut microbiota sampling using shape memory alloy spring - Rehan, Muhammad; Al‐Bahadly, Ibrahim; Thomas, David G.; Avci, Ebubekir (The international journal of medical robotics + computer assisted surgery, 2020)
Background Human gut microbiota can provide lifelong health information and even influence mood and behaviour. We currently lack the tools to obtain a microbial sample, directly from the small intestine, without contamination. Methods Shape memory alloy springs are used in concentric configuration to develop an axial actuator. A novel design of sampling mechanism is fabricated for collecting the sample from the gut. Storage chamber (500 µl) is used to protect the sample from downstream contamination. Results The developed actuator occupies a small space (5 × Ø5.75 mm) and produces sufficient output force (1.75 N) to operate the sampling mechanism. A non‐invasive capsule robot was tested ex vivo on the animal intestine, and it captured an average of 134 µl content which was sufficient for microbiome assessment. Conclusions Laboratory testing revealed that the collected sample had an amino acid signature indicative of microbiota, mucus and digesta, which provided a proof of concept for the proposed design.